Prevalence of Ciprofloxacin and Nalidixic Acid Resistant Salmonella enterica serovar Typhi in Bangladesh (Bangladesh Journal of Microbiology, 2012)
A total of 1,059 Salmonella enterica serovar Typhi were isolated from blood samples during January 2006 to  October 2007 from urban rural facilities in Dhaka, Bangladesh, of which 980 (92.5%) isolates were nalidixic  acid resistant. The minimum inhibitory concentrations (MIC) of ciprofloxacin (CIP) were determined for 127  nalidixic acid resistant Salmonella enterica serovar Typhi (NARST) strains (every fifth) isolated during 2006.  Nine isolates were found to be resistant against CIP (3%) with high MIC (12 - >32 ?g/mL). Only four isolates  were found to be sensitive (MIC